Pelatihan Penggunaan Ms. Powerpoint Sebagai Media Presentasi Atraktif Bagi Kelompok Masyarakat Peduli Iklim Bumiku Satu RW 01 - Fajar Agustini; Euis Widanengsih; Henny Destiana; Aryo Tunjung Kusumo (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Temperature changes that occur on Earth due to human activities that cause pollution result in climate change in the hemisphere. The increase in climate has resulted in threats and risks of disasters, such as floods, landslides, droughts, and human health problems. The Climate Care Community Group for Our Earth One RW 01 is an organization that serves as a forum for communication and coordination for residents of RW 01 to realize the climate village program in Gaga Village, Larangan District, Tangerang City. Previous programs have been running and are continuing, such as farmer women's groups, waste banks, making bio pores, clean water channel programs, and climate village programs which aim to create clean, beautiful, green, and fresh villages. The need for fresh air and a green environment is critical now, as seen from the many city parks built by the central and regional governments. The importance of clean air and greenery makes many residents who are members of community groups concerned about the environment. The group makes greenery in the neighborhood to provide coolness and serenity. The Community Group Concerning the Climate of Our Earth One RW 01 was formed to create a clean, green, and relaxed environment so that a good climate for the health and development of its inhabitants will be formed. Many activities have been carried out, such as requiring every house to have at least 1 tree and planting gardens in every space in Larangan Village, Gaga. However, the problems faced by partners are the membership which is still tiny compared to residents in RW 01, and the need for more understanding of residents about how to present the importance of caring for the climate. Therefore we took the initiative to conduct training using power points to attract residents' interest to participate in the Community Group Concerning the Climate of Our Earth One RW 01.